Elastocaloric effect and superelastic stability in Ni–Mn–In–Co polycrystalline Heusler alloys: hysteresis and strain-rate effects - Binfeng Lu (Nature Portfolio, 2017)
Abstract Controlling material hysteresis and working frequency variability are fundamentally important for refrigeration cycle efficiency and power density in solid-state cooling systems. For elastocaloric cooling, understanding the relationship between the width of the stress hysteresis and elastocaloric behaviour during superelastic cycles under varied strain rates is important. In this work, we report the effects of strain rate effects on the superelastic and elastocaloric responses in Ni45Mn50−xInxCo5 (x = 13.6–14.0 in at%) polycrystalline alloys. We observed a strong correlation between stress hysteresis and superelastic stability during mechanical cycling under increasing strain rates. Excellent transformation reversibility and stable superelastic responses are observed for x = 13.6 with a narrow hysteresis (49 MPa), whereas transformation irreversibility and dramatically deteriorated superelastic stability occur for x = 13.8, with a wide hysteresis (138 MPa). Furthermore, isothermal loading–unloading cycles under increasing and constant maximum applied stress were performed for the x = 13.6 samples, with a combination of low transformation stress and small transformation hysteresis. We suggest that a balance between transformation strain and hysteresis energy loss is fundamental to achieving a high coefficient of performance for elastocaloric materials.